2014
DOI: 10.1136/archdischild-2012-302066
|View full text |Cite
|
Sign up to set email alerts
|

Moving beyond prevalence studies: screening and interventions for children with disabilities in low-income and middle-income countries

Abstract: Research understanding the lives of children with disabilities in low-income and middle-income countries has predominantly focused on prevalence studies with little progress on evidence-based service development. At the same time, global attention in child health has shifted from child survival strategies to those that bring child survival and development together. This review examines whether intervention research can be better aligned with current theoretical constructs of disability and international guidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 67 publications
2
44
0
1
Order By: Relevance
“…The few studies which have included caregiver outcomes for home and community-based interventions, have generally focussed on one or two measures of improvements in maternal knowledge and stress, and parent satisfaction with services [43] [20] [4446]. In our study, the reported improvement in knowledge and confidence in caring for their child is encouraging; and arguably, more importantly, the emphasis on problem solving and caregiver empowerment, within a support group setting, has the potential to offer a more sustainable mechanism for improving long term outcomes for the child and family.…”
Section: Discussionmentioning
confidence: 99%
“…The few studies which have included caregiver outcomes for home and community-based interventions, have generally focussed on one or two measures of improvements in maternal knowledge and stress, and parent satisfaction with services [43] [20] [4446]. In our study, the reported improvement in knowledge and confidence in caring for their child is encouraging; and arguably, more importantly, the emphasis on problem solving and caregiver empowerment, within a support group setting, has the potential to offer a more sustainable mechanism for improving long term outcomes for the child and family.…”
Section: Discussionmentioning
confidence: 99%
“…24 This addition is expected to improve the capacity of countries to care for children with disabilities and implement rehabilitative strategies. 25 Supporting maternal mental health Starting with Bowlby's seminal work on attachment and loss, 3 evidence has accumulated about the adverse effects of maternal depressive symptoms on early child development and quality of parenting. Between a third and a fifth of pregnant women and mothers of newborns experience serious mental health problems that can be recognised through use of simple reliable tools.…”
Section: Priorities For Interventionmentioning
confidence: 99%
“…This phrase was used by Charlton (1998) and Werner (1998) who focussed on human rights for people with disability. They wanted to communicate the idea that no action or policy should be decided by any representative, without the full and direct participation of members affected by that action or policy.…”
Section: Introductionmentioning
confidence: 99%
“…The CARD programme, like EDR, sought to reflect the ideology that 'no action or policy should be decided by any representative without the full and direct participation of members affected by that action or policy' (Werner, 1998), by not only engaging individuals with disability at every stage of the research, from concept to outcome, but also by promoting partnerships with service providers and disability researchers/academics who were also stakeholders in this action. In other words, 'Nothing about us without us all.'…”
Section: Introductionmentioning
confidence: 99%